A Comprehensive Comparison of DNA Extraction Using Fresh and Stored Bloods in Molecular Hematology Diagnostic Study - Hassan, Siti Nazihahasma; Mohamad, Suharni; Hassan, Rosline; Ghazali, Selamah; Rahman, Wan Suriana Wan Ab (Bangladesh Journal of Medical Science, 2018)
Objective: Blood is the main source of DNA in molecular biology. It provides a high DNA quality and quantity. In this study, we compare the quality and quantity of DNA isolated from stored blood that has been kept at -40°C for one-year to that of fresh blood. Materials and Methods: Twelve fresh and stored blood samples were randomly selected for this study. Nucleo Spin® Blood L kit was used to isolate the DNA from the samples. The integrity and intensity of DNA were examined through 1.6% agarose gel precast with SYBR® safe DNA stain. The DNA samples were further examined through PCR amplification and Sanger sequencing. Results: There was no significant difference in quality and quantity of isolated DNA from fresh blood and stored blood samples. The high intensity of an intact DNA band as well as the success in PCR amplification and sequencing are indicators of high DNA quality. Conclusion: Proper storage of patients’left-over whole blood sample at -40°C offers an acceptable alternative for DNA resources in molecular study. Bangladesh Journal of Medical Science Vol.17(3) 2018 p.424-432